Evaluating the Impact of a Video-Based Chest Examination Assignment on Self-Directed Learning and Clinical Skills Development in Second-Year Medical Students at the Nelson Mandela School of Medicine (Bangladesh Journal of Medical Science, 2026)
Background In undergraduate medical education, fostering self-directed learning (SDL) behaviours and clinical competence is essential yet challenging, particularly in traditional physical examination training, which often lacks opportunities for repeated practice, reflection, and feedback. This study evaluated the impact of a structured, team-based, video-recorded chest examination assignment on second-year medical students’ SDL, clinical confidence, and skill development, framed using the Kirkpatrick Model of Learning Evaluation. Methods A mixed-methods pre-post intervention study was conducted at the Nelson Mandela School of Medicine in March 2025 with 250 second-year medical students. Students worked in small groups to complete a chest examination video, incorporating peer assessment and final submission. Pre- and postintervention surveys (n = 99 and n = 150, respectively) measured SDL behaviours and clinical confidence using matched Likert-scale items. OSCE scores were compared between the 2024 (control) and 2025 (intervention) cohorts. Open-ended responses underwent thematic analysis to explore student experiences. Results Significant improvements were observed in SDL behaviours (t (4) = 5.49, p = 0.0015) and clinical confidence (t (5) = 7.40, p = 0.0007), particularly in goal setting, feedback seeking, procedural accuracy, and communication. Perceived clinical competence and teamwork also improved, though not significantly. OSCE scores remained stable across cohorts (mean = 76%, p = 1.00), suggesting enhanced learning behaviours without loss of performance. Thematic analysis revealed four themes - evolving perceptions, learning outcomes, practical challenges, and curricular reflections mapped to Kirkpatrick’s four levels: Reaction, Learning, Behaviour, and Results. Conclusion: The video-based assignment enhanced SDL behaviours, confidence, and reflective capacity, even without measurable OSCE score changes. Students valued the peer-driven, engaging, and supportive approach for bridging knowledge and clinical application. Video-based peer learning is a scalable strategy to promote reflective, self-directed learning and procedural mastery in early clinical education, aligning with competencybased education and preparing students for lifelong clinical growth.BJMS, Vol. 25 No. 01 January’26 Page : 150-162